An all-in-one complementary electrochromic device and a preparation method thereof

CN122962862APending Publication Date: 2026-10-23ZHEJIANG UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611135955.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-29
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0005]本发明的目的在于提供一种一体式互补型电致变色器件及其制备方法,解决现有小分子电致变色材料稳定性差的技术问题

Benefits of technology

本发明通过对对苯二胺中间共轭π桥进行修饰,桥连具有独特的三维“螺旋桨”扭曲构型的四苯基乙烯,产生巨大的空间位阻,这不仅有效阻断了分子间的π-π堆叠,还保护了三苯胺端基氧化生成的自由基阳离子,并在苯胺端上接上四个甲氧基,以降低氧化电位,极大抑制了不可逆的电化学偶联副反应,制备的三苯胺衍生物在低驱动电压下可从淡黄到黑。组装基于此化合物材料与乙基紫精共混的一体式互补型液态器件或凝胶准固态器件,凝胶准固态器件更接近实际应用,相对于传统的三明治结构,成本低且操作简单,所制备的器件兼具优异的电致变色性能和电化学性能,不仅在低驱动电压下展现出较高的光学对比度,中性态下为黄色,氧化态下为深蓝黑色,且具有合适的响应时间、较好的循环稳定性,在数千次循环后仍能保持极高的透过率循环稳定性,在智能节能窗、防眩目后视镜等电致变色领域具有潜在的应用前景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122962862A_ABST
    Figure CN122962862A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of organic polymer chemistry, and discloses an integrated complementary electrochromic device and a preparation method thereof. The application modifies the intermediate conjugated π bridge in p-phenylenediamine, and connects tetraphenyl ethylene with a unique three-dimensional propeller twist configuration, so as to produce huge steric hindrance. The steric hindrance not only effectively blocks the π-π stacking between molecules, but also protects the free radical cation generated by the oxidation of the triphenylamine end group. In addition, four methoxy groups are connected to the aniline end to reduce the oxidation potential and greatly inhibit the irreversible electrochemical coupling side reaction. The integrated complementary liquid device or gel quasi-solid device based on the compound material and ethyl viologen blending is assembled. Compared with the traditional sandwich structure, the cost is low and the operation is simple. The high transmittance cycle stability can be maintained after thousands of cycles, and the integrated complementary electrochromic device has a potential application prospect in the field of intelligent energy-saving windows, anti-dazzling rearview mirrors and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of organic polymer chemistry, and in particular to an integrated complementary electrochromic device and its preparation method. Background Technology

[0002] Stimulus-responsive functional materials have become a research hotspot in recent years due to their potential applications in displays, sensing, and information storage. Electrically stimulating materials are characterized by precise control, timely response, and high repeatability. Currently, electrochromic (EC) materials are among the most studied. EC materials offer advantages such as fast response time, controllable conditions, and rich color variations, and have already achieved commercial applications in areas such as smart windows in buildings, anti-glare rearview mirrors, and electronic tags.

[0003] Electrochromism refers to the stable and reversible color change of a material's optical properties (such as reflectivity, transmittance, and absorptivity) under the influence of an applied electric field. Among numerous organic electrochromic materials, triphenylamine (TPA) derivatives have been widely studied due to their excellent hole transport capabilities, ease of modification, and anodic coloring properties; while viologen compounds are classic cathodic coloring materials. Combining these two to construct complementary electrochromic devices can significantly improve the device's stability and optical modulation.

[0004] However, existing triphenylamine-based complementary liquid devices still face some technical bottlenecks in practical applications: many highly conjugated triphenylamine derivatives have rigid planar configurations, and during long-term redox electrochemical polarization, the generated free radical cations are prone to intermolecular coupling side reactions or close packing, leading to poor device cycle stability and decreased coloring efficiency. Furthermore, how to further shorten the response time of liquid devices to meet the requirements of rapid switching remains a key research direction in this field. Summary of the Invention

[0005] The purpose of this invention is to provide an integrated complementary electrochromic device and its preparation method, thereby solving the technical problem of poor stability of existing small molecule electrochromic materials.

[0006] To achieve the above-mentioned objectives, the present invention provides the following technical solution: The present invention provides an integrated complementary electrochromic device, comprising, in sequence: a first transparent conductive layer, a mixed electrochromic layer and a second transparent conductive layer, wherein the mixed electrochromic layer comprises an anode material, a cathode material, and a mixture of a supporting electrolyte and a solvent, wherein the anode material is a transparent-black triphenylamine derivative; The transparent-black triphenylamine derivative has the structure shown in Formula I: Formula I.

[0007] Furthermore, in the integrated complementary electrochromic device, the preparation method of the transparent-black triphenylamine derivative includes the following steps: Under a protective atmosphere, 4,4-dimethoxydiphenylamine, 1,2-bis(4-bromophenyl)-1,2-diphenylene, basic additives, organophosphorus ligands, catalysts and organic solvents were mixed and coupled to obtain the transparent-black triphenylamine derivative. The molar ratio of the 4,4-dimethoxydiphenylamine to the 1,2-bis(4-bromophenyl)-1,2-diphenylene is 2.5~3:1; The alkaline additive includes one or more of sodium tert-butoxide, potassium tert-butoxide, and cesium carbonate; The molar ratio of 4,4-dimethoxydiphenylamine to the alkaline additive is 1:1~2; The organophosphine ligands include one or more of tri-tert-butylphosphine, di-tert-butylneoprenephosphine, and Xphos. The catalyst comprises tris(dibenzylacetone)dipalladium and / or palladium acetate; The molar ratio of the 4,4-dimethoxydiphenylamine, the organophosphine ligand, and the catalyst is 5~10:0.5~2:0.1~1; The coupling reaction is carried out at a temperature of 100-120°C for 18-22 hours.

[0008] Furthermore, in the integrated complementary electrochromic device, the hybrid electrochromic layer includes a liquid hybrid electrochromic layer or a quasi-solid hybrid electrochromic layer.

[0009] Furthermore, in the integrated complementary electrochromic device, the quasi-solid-state hybrid electrochromic layer also includes polymethyl methacrylate or polyvinylidene fluoride. The mass of the polymethyl methacrylate or the polyvinylidene fluoride is independently 20-30% of the sum of the masses of the supporting electrolyte and the solvent.

[0010] Furthermore, in the integrated complementary electrochromic device, the cathode material includes ethyl viologen and / or heptyl viologen; The molar ratio of the anode material to the cathode material is 1:2 to 4, and the concentration of the anode material in the mixture of supporting electrolyte and solvent is 0.005 to 0.02 mol / L.

[0011] Furthermore, in the integrated complementary electrochromic device, the supporting electrolyte includes one or more of tetrabutylammonium tetrafluoroborate, tetrabutylammonium hexafluorophosphate, and lithium perchlorate; The concentration of the supporting electrolyte in the mixture of supporting electrolyte and solvent is 0.01~0.02 mol / L.

[0012] Furthermore, in the integrated complementary electrochromic device, the first transparent conductive layer and the second transparent conductive layer independently include ITO conductive glass, FTO glass, or PET film.

[0013] Furthermore, in the integrated complementary electrochromic device, the thickness of the hybrid electrochromic layer is 1 mm.

[0014] Furthermore, in the integrated complementary electrochromic device, an adhesive layer is also included between the first transparent conductive layer and the hybrid electrochromic layer; And / or, an adhesive layer may be further included between the hybrid electrochromic layer and the second transparent conductive layer.

[0015] This invention also provides a method for fabricating an integrated complementary electrochromic device, comprising the following steps: An electrochromic mixture is obtained by mixing the anode material, cathode material, supporting electrolyte, and solvent. An electrochromic mixture is coated onto the surface of a first or second transparent conductive layer, and the other side of the transparent conductive layer is covered onto the coated electrochromic mixture surface. The device is then encapsulated to obtain an integrated complementary electrochromic device.

[0016] As can be seen from the above technical solution, compared with the prior art, the present invention has the following beneficial effects: This invention modifies the intermediate conjugated π-bridge of p-phenylenediamine to bridge tetraphenylethylene, which has a unique three-dimensional "propeller" twisted configuration, generating huge steric hindrance. This not only effectively blocks the π-π stacking between molecules, but also protects the free radical cations generated by the oxidation of the triphenylamine terminal group. Furthermore, four methoxy groups are attached to the aniline terminal to reduce the oxidation potential, greatly suppressing irreversible electrochemical coupling side reactions. The prepared triphenylamine derivative can range from pale yellow to black under low driving voltage. Assemble integrated complementary liquid devices or gel quasi-solid devices based on this compound material blended with ethyl viologen. Gel quasi-solid devices are closer to practical applications. Compared with the traditional sandwich structure, they are lower in cost and simpler to operate. The prepared devices have both excellent electrochromic and electrochemical performance. They not only exhibit high optical contrast at low driving voltage, but also appear yellow in the neutral state and deep blue-black in the oxidized state. They also have suitable response time and good cycling stability, maintaining extremely high transmittance cycling stability even after thousands of cycles. They have potential application prospects in electrochromic fields such as smart energy-saving windows and anti-glare rearview mirrors. Attached Figure Description

[0017] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below.

[0018] Figure 1 To prepare the transparent-black triphenylamine derivative of Example 1 1 1H NMR spectrum; Figure 2 The mass spectrum of the transparent-black triphenylamine derivative of Preparation Example 1; Figure 3 The graph shows the cyclic voltammetry curves of the liquid device in Example 1 at different scan rates. Figure 4 The image shows the UV-Vis absorption spectra of the liquid device in Example 1 at different voltages, and the inset shows the color photographs of the device at different voltages. Figure 5 The transmittance curves of the liquid device in Example 1 under different voltages and different wavelengths are shown. Figure 6 This is a test graph showing the response time of the liquid device in Example 1 at the 605nm wavelength. Figure 7 This is a test graph showing the cyclic stability of the liquid device in Example 1 at 605nm wavelength; Figure 8 This is a test graph showing the response time of the gel quasi-solid-state device in Example 2 at the 608nm wavelength. Figure 9 This is a test graph showing the cyclic stability of the gel quasi-solid-state device in Example 2 at the 608nm wavelength. Detailed Implementation

[0019] The present invention provides an integrated complementary electrochromic device, comprising, in sequence: a first transparent conductive layer, a mixed electrochromic layer and a second transparent conductive layer, wherein the mixed electrochromic layer comprises an anode material, a cathode material, and a mixture of a supporting electrolyte and a solvent, wherein the anode material is a transparent-black triphenylamine derivative; The transparent-black triphenylamine derivative has the structure shown in Formula I: Formula I.

[0020] In this invention, the preparation method of the transparent-black triphenylamine derivative includes the following steps: Under a protective atmosphere, 4,4-dimethoxydiphenylamine, 1,2-bis(4-bromophenyl)-1,2-diphenylene, basic additives, organophosphorus ligands, catalysts and organic solvents were mixed and coupled to obtain the transparent-black triphenylamine derivative. Unless otherwise specified, nitrogen may be used as the protective atmosphere. The 4,4-dimethoxydiphenylamine has the structure shown in Formula II: Formula II; The 1,2-bis(4-bromophenyl)-1,2-diphenylene has the structure shown in Formula III: Formula III; The molar ratio of the 4,4-dimethoxydiphenylamine to the 1,2-bis(4-bromophenyl)-1,2-diphenylene is preferably 2.5 to 3:1, more preferably 2.5 to 2.7:1, and even more preferably 2.5:1; The alkaline additive preferably includes one or more of sodium tert-butoxide, potassium tert-butoxide, and cesium carbonate, more preferably sodium tert-butoxide, potassium tert-butoxide, or cesium carbonate, and more preferably sodium tert-butoxide. The molar ratio of the 4,4-dimethoxydiphenylamine to the alkaline additive is preferably 1:1 to 2, more preferably 1:1 to 1.5, and even more preferably 1:1; The organophosphine ligand preferably includes one or more of tri-tert-butylphosphine, di-tert-butylneoprene, and Xphos, more preferably tri-tert-butylphosphine, di-tert-butylneoprene, or Xphos, and more preferably tri-tert-butylphosphine; the tri-tert-butylphosphine is added in the form of a commercially available solution dissolved in 10% n-hexane. The catalyst preferably comprises tris(dibenzylacetone)dipalladium and / or palladium acetate, and more preferably tris(dibenzylacetone)dipalladium; In this invention, the molar ratio of the 4,4-dimethoxydiphenylamine, the organophosphorus ligand, and the catalyst is preferably 5~10:0.5~2:0.1~1, more preferably 5~6:0.6~0.8:0.2~0.4, and even more preferably 5.1:0.68:0.23; The organic solvent preferably includes toluene and / or 1,4-dioxane, and more preferably toluene; The molar ratio of the 4,4-dimethoxydiphenylamine to the volume of the organic solvent is preferably 4-6 mmol:50-70 mL, more preferably 5-5.5 mmol:50-60 mL, and even more preferably 5.1 mmol:50 mL. The preferred reaction temperature for the coupling reaction is 100~120℃, more preferably 110~120℃, and even more preferably 110℃; the preferred reaction time is 18~22h, more preferably 20~22h, and even more preferably 22h. The coupling reaction is followed by post-processing, specifically including the following steps: After the reaction is complete, the mixture is cooled to room temperature, the reaction liquid is extracted with dichloromethane, and then washed with saturated brine. The extracted organic phase is then dried with anhydrous sodium sulfate, filtered, and the filtrate is obtained. Column chromatography is performed using silica gel as the stationary phase and ethyl acetate and petroleum ether as the mobile phase. The conditions for the post-processing are not limited; any method well-known in the art can be used. In the specific embodiment, the saturated brine wash is performed three times, and the volume ratio of ethyl acetate to petroleum ether is 1:7.

[0021] In this invention, the hybrid electrochromic layer preferably comprises a liquid hybrid electrochromic layer or a quasi-solid hybrid electrochromic layer, and more preferably a quasi-solid hybrid electrochromic layer.

[0022] In this invention, the quasi-solid-state mixed electrochromic layer preferably further includes polymethyl methacrylate or polyvinylidene fluoride, and more preferably polymethyl methacrylate.

[0023] In this invention, the mass of the polymethyl methacrylate or the polyvinylidene fluoride is preferably 20-30% of the sum of the masses of the supporting electrolyte and the solvent, more preferably 20-25%, and even more preferably 20%.

[0024] In this invention, the cathode material preferably includes ethyl viologen and / or heptyl viologen, and more preferably ethyl viologen.

[0025] In this invention, the molar ratio of the anode material to the cathode material is preferably 1:2 to 4, more preferably 1:3 to 4, and even more preferably 1:4.

[0026] In this invention, the concentration of the anode material in the mixture of supporting electrolyte and solvent is preferably 0.005~0.02 mol / L, more preferably 0.005~0.01 mol / L, and even more preferably 0.0075 mol / L.

[0027] In this invention, the supporting electrolyte preferably includes one or more of tetrabutylammonium tetrafluoroborate, tetrabutylammonium hexafluorophosphate, and lithium perchlorate, more preferably includes tetrabutylammonium tetrafluoroborate, tetrabutylammonium hexafluorophosphate, or lithium perchlorate, and more preferably tetrabutylammonium tetrafluoroborate.

[0028] In this invention, the concentration of the supporting electrolyte in the mixture of supporting electrolyte and solvent is preferably 0.01~0.02 mol / L, more preferably 0.01~0.015 mol / L, and even more preferably 0.01 mol / L.

[0029] In this invention, the first transparent conductive layer and the second transparent conductive layer are preferably independent of each other, including ITO conductive glass, FTO glass or PET film, and more preferably ITO conductive glass.

[0030] In this invention, the thickness of the hybrid electrochromic layer is preferably 1 mm.

[0031] In this invention, an adhesive layer is further included between the first transparent conductive layer and the hybrid electrochromic layer; And / or, an adhesive layer may be further included between the hybrid electrochromic layer and the second transparent conductive layer.

[0032] In this invention, the adhesive layer is not limited, and any material well known in the art can be used. In a specific embodiment, 3M adhesive is used.

[0033] This invention also provides a method for fabricating an integrated complementary electrochromic device, comprising the following steps: An electrochromic mixture is obtained by mixing the anode material, cathode material, supporting electrolyte, and solvent. An electrochromic mixture is coated onto the surface of a first or second transparent conductive layer, and the other side of the transparent conductive layer is covered onto the coated electrochromic mixture surface. The device is then encapsulated to obtain an integrated complementary electrochromic device.

[0034] In this invention, the mixing conditions are not limited, and any well-known method of uniform mixing in the art can be used. Specifically, in this embodiment, ultrasonic dissolution at room temperature is employed.

[0035] In this invention, the encapsulation conditions are not limited; any adhesive layer well-known in the art can be used for bonding in room temperature air. Specifically, in this embodiment, 3M adhesive is used for encapsulation.

[0036] In this invention, unless otherwise specified, the source of raw materials and other parameters are not limited, and solutions well known in the art can be used.

[0037] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0038] Preparation Example 1

[0039] This preparation example provides a method for preparing a transparent-to-black triphenylamine derivative with low driving voltage, comprising the following steps: To a 100 mL double-necked round-bottom flask, add 4,4-dimethoxydiphenylamine (1.17 g, 5.10 mmol), 1,2-bis(4-bromophenyl)-1,2-diphenylene (1 g, 2.04 mmol), sodium tert-butoxide (0.49 g, 5.10 mmol), tri-tert-butylphosphine solution (0.14 g, 0.68 mmol), and tris(dibenzylacetone)dipalladium (0.20 g, 0.23 mmol), followed by 50 mL of anhydrous toluene. The mixture was heated to reflux at 110 °C for 22 h. After the reaction was complete, the mixture was cooled to room temperature, and the reaction liquid was extracted with dichloromethane and washed three times with saturated brine. The extracted organic phase was then dried with anhydrous sodium sulfate and filtered to obtain the filtrate. Using silica gel as the stationary phase and ethyl acetate and petroleum ether as the mobile phase, column chromatography was performed at an ethyl acetate:petroleum ether ratio of 1:7 to obtain 0.62 g of the yellow solid compound TPPA-E with the structure shown in Formula I, in a yield of 45%.

[0040] The TPPA-E prepared in Preparation Example 1 was subjected to... 1 1H NMR and mass spectrometry characterization, results are as follows Figure 1 , Figure 2 As shown.

[0041] Preparation Example 1 1 The 1H NMR characterization data are shown below: 1 H NMR (400 MHz, CDCl3) δ 7.20 (s, 14H), 6.95 (dd, J = 15.2, 9.1 Hz, 12H), 6.87 (d, J = 8.8 Hz, 8H), 3.71 (d, J = 1.3 Hz, 12H). MS (ESI) m / z calculated.For (C 54 H 46 N2O4):786.3458, found: 786.3530. Example 1 Using TPPA-E prepared in Example 1 as the anode material and ethyl viologen as the cathode material, 18 mg (0.0075 mol / L) of TPPA-E and 45 mg (0.03 mol / L) of ethyl viologen were dissolved in 3 mL (0.01 mol / L) of γ-butyrolactone electrolyte solution containing tetrabutylammonium tetrafluoroborate. The solution was ultrasonically dissolved and stirred at room temperature, and then dropped onto an ITO (2.5 × 4 cm) glass plate using a dropper. The conductive surfaces of another ITO glass plate were then bonded together with 3M adhesive at room temperature for encapsulation. After natural drying, an integrated complementary electrochromic liquid device was obtained, with a mixed electrochromic layer thickness of 1 mm.

[0042] The electrochemical and electrochromic properties of the electrochromic device of Example 1 were tested.

[0043] (1) Cyclic voltammetry performance test

[0044] 3.293 g (0.10 mol / L) of tetrabutylammonium tetrafluoroborate was added to a 100 mL volumetric flask and diluted to volume with γ-butyrolactone to serve as a blank supporting electrolyte solution. The liquid device assembled in Example 1 was subjected to electrochemical testing. Cyclic voltammetry curves were measured from -0.4 to 1.2 V at scan rates of 25 mV / s, 50 mV / s, 100 mV / s, 150 mV / s, and 200 mV / s. The test results are as follows: Figure 3 As shown.

[0045] Depend on Figure 3 As can be seen, the cyclic voltammetry curves show obvious reversible redox peaks, and these peaks change regularly with increasing scan rate. This indicates that the triphenylamine derivative material prepared in Example 1 has good electrochemical performance and redox reversibility.

[0046] (2) Ultraviolet-Visible Absorption Spectroscopy Test

[0047] 3.293 g (0.10 mol / L) of tetrabutylammonium tetrafluoroborate was added to a 100 mL volumetric flask and diluted to volume with γ-butyrolactone to serve as a blank supporting electrolyte solution. The liquid device assembled in Example 1 was subjected to UV-Vis absorption spectroscopy at different voltages, measured in 0.1 V intervals from 0 V to 1.2 V. The test results are as follows: Figure 4 As shown.

[0048] Depend on Figure 4 The ultraviolet-visible absorption spectrum shows that the device is pale yellow in the neutral state, and the absorption peak increases with the applied voltage. The device appears dark blue-black in the oxidized state. When the voltage is removed or a reverse voltage is applied, the color gradually changes from dark blue-black to pale yellow. This process repeats, demonstrating good electrochromic reversibility.

[0049] (3) Electrochromic performance test

[0050] 3.293 g (0.10 mol / L) of tetrabutylammonium tetrafluoroborate was added to a 100 mL volumetric flask and diluted to volume with γ-butyrolactone to serve as a blank supporting electrolyte solution. The transmittance of the liquid device assembled in Example 1 was tested at different voltages. The transmittance curves of the device in the 400–1000 nm wavelength range were measured under the following conditions: neutral state at 0.0 V, oxidized state at 1.1 V, and under a reverse voltage of -0.4 V. The test results are shown below. Figure 5 As shown.

[0051] Depend on Figure 5 As can be seen from the transmittance change curve, the transmittance contrast of the device in Example 1 at 605nm in the 0.0V neutral state and the 1.1V oxidized state is about 80%, and it has a very obvious color change.

[0052] (4) Electrochromic performance test

[0053] 3.293 g (0.10 mol / L) of tetrabutylammonium tetrafluoroborate was added to a 100 mL volumetric flask and diluted to volume with γ-butyrolactone to serve as the blank supporting electrolyte solution. The electrochromic response time and cyclic stability of the liquid device assembled in Example 1 were tested using a step voltage mode. The coloring voltage was 1.1 V applied for 10 s; the decolorization voltage was -0.4 V applied for 10 s. The test results are as follows: Figure 6 , Figure 7 As shown.

[0054] Depend on Figure 6 and Figure 7 It can be seen that the device in Example 1 has a coloring time of 6.2s and a fading time of 8.6s in the 605nm band, and its optical contrast ratio is 46.9%. After 1500 cycles, its optical contrast ratio remains at 77.2% of the original value, which shows that it has a reasonable response time and good cycle stability.

[0055] Example 2

[0056] Using TPPA-E prepared in Example 1 as the anode material and ethyl viologen as the cathode material, 18 mg (0.0075 mol / L) of TPPA-E and 45 mg (0.03 mol / L) of ethyl viologen were dissolved in 3 mL (0.01 mol / L) of γ-butyrolactone electrolyte solution containing tetrabutylammonium tetrafluoroborate. 20% by weight of polymethyl methacrylate (PMMA, manufacturer: Anage Chemicals, grade DK200086) was added, and the mixture was stirred at room temperature for 2 hours. The solution was then dropped onto ITO (2.5 × 4 cm) glass using a dropper. The conductive surfaces of another ITO glass piece were bonded together with 3M adhesive in air at room temperature for encapsulation. After natural drying, an integrated complementary electrochromic gel quasi-solid-state device was obtained, with a mixed electrochromic layer thickness of 1 mm.

[0057] The electrochromic performance of the electrochromic device in Example 2 was tested.

[0058] 3.293 g (0.10 mol / L) of tetrabutylammonium tetrafluoroborate was added to a 100 mL volumetric flask and diluted to volume with γ-butyrolactone to serve as a blank supporting electrolyte solution. The gel quasi-solid-state device assembled in Example 2 was subjected to electrochromic response time and cyclic stability tests using a step voltage mode. The coloring voltage was 1.1 V, applied for 10 s; the decolorization voltage was -0.4 V, applied for 10 s. The test results are as follows: Figure 8 , Figure 9 As shown.

[0059] Depend on Figure 8 and Figure 9 It can be seen that the device in Example 2 has a coloring time of 7.1s and a fading time of 8.0s in the 608nm band, and its optical contrast ratio is 28.7%. After 2000 cycles, its optical contrast ratio remains at 67.5% of the original value, which shows that it has a reasonable response time and good cycle stability.

[0060] As demonstrated by the above examples, this invention provides an integrated complementary electrochromic liquid device. The anode material is modified by altering the conjugated π-bridge in the middle of p-phenylenediamine, bridging tetraphenylethylene with a unique three-dimensional "propeller" twisted configuration, and attaching four methoxy groups to the aniline end to reduce the oxidation potential and greatly suppress irreversible electrochemical coupling side reactions. The electrochromic device maintains extremely high transmittance cycling stability even after thousands of cycles. Compared to traditional sandwich structures, the integrated complementary liquid device and gel quasi-solid device of this invention are low-cost and simple to operate. The fabricated devices exhibit suitable response times, good cycling stability, and low operating voltages, showing broad application prospects in the display field.

[0061] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. An integrated complementary electrochromic device, comprising, in sequence: The first transparent conductive layer, the mixed electrochromic layer, and the second transparent conductive layer are characterized in that the mixed electrochromic layer comprises an anode material, a cathode material, and a mixture of a supporting electrolyte and a solvent, wherein the anode material is a transparent-black triphenylamine derivative; The transparent-black triphenylamine derivative has the structure shown in Formula I: Formula I.

2. The integrated complementary electrochromic device according to claim 1, characterized in that, The preparation method of the transparent-black triphenylamine derivative includes the following steps: Under a protective atmosphere, 4,4-dimethoxydiphenylamine, 1,2-bis(4-bromophenyl)-1,2-diphenylene, basic additives, organophosphorus ligands, catalysts and organic solvents were mixed and coupled to obtain the transparent-black triphenylamine derivative. The molar ratio of the 4,4-dimethoxydiphenylamine to the 1,2-bis(4-bromophenyl)-1,2-diphenylene is 2.5~3:1; The alkaline additive includes one or more of sodium tert-butoxide, potassium tert-butoxide, and cesium carbonate; The molar ratio of 4,4-dimethoxydiphenylamine to the alkaline additive is 1:1~2; The organophosphine ligands include one or more of tri-tert-butylphosphine, di-tert-butylneoprenephosphine, and Xphos. The catalyst comprises tris(dibenzylacetone)dipalladium and / or palladium acetate; The molar ratio of the 4,4-dimethoxydiphenylamine, the organophosphine ligand, and the catalyst is 5~10:0.5~2:0.1~1; The coupling reaction is carried out at a temperature of 100-120°C for 18-22 hours.

3. The integrated complementary electrochromic device according to claim 1, characterized in that, The hybrid electrochromic layer includes a liquid hybrid electrochromic layer or a quasi-solid hybrid electrochromic layer.

4. The integrated complementary electrochromic device according to claim 3, characterized in that, The quasi-solid hybrid electrochromic layer also includes polymethyl methacrylate or polyvinylidene fluoride; The mass of the polymethyl methacrylate or the polyvinylidene fluoride is independently 20-30% of the sum of the masses of the supporting electrolyte and the solvent.

5. The integrated complementary electrochromic device according to any one of claims 1 to 4, characterized in that, The cathode material includes ethyl viologen and / or heptyl viologen; The molar ratio of the anode material to the cathode material is 1:2 to 4, and the concentration of the anode material in the mixture of supporting electrolyte and solvent is 0.005 to 0.02 mol / L.

6. The integrated complementary electrochromic device according to claim 5, characterized in that, The supporting electrolyte includes one or more of tetrabutylammonium tetrafluoroborate, tetrabutylammonium hexafluorophosphate, and lithium perchlorate; The concentration of the supporting electrolyte in the mixture of supporting electrolyte and solvent is 0.01~0.02 mol / L.

7. The integrated complementary electrochromic device according to claim 1, characterized in that, The first transparent conductive layer and the second transparent conductive layer are independent of each other, including ITO conductive glass, FTO glass, or PET film.

8. The integrated complementary electrochromic device according to claim 1, characterized in that, The thickness of the hybrid electrochromic layer is 1 mm.

9. The integrated complementary electrochromic device according to claim 1, characterized in that, An adhesive layer is also included between the first transparent conductive layer and the hybrid electrochromic layer; And / or, an adhesive layer may be further included between the hybrid electrochromic layer and the second transparent conductive layer.

10. A method for preparing the integrated complementary electrochromic device according to any one of claims 1 to 9, characterized in that, Includes the following steps: An electrochromic mixture is obtained by mixing the anode material, cathode material, supporting electrolyte, and solvent. An electrochromic mixture is coated onto the surface of a first or second transparent conductive layer, and the other side of the transparent conductive layer is covered onto the coated electrochromic mixture surface. The device is then encapsulated to obtain an integrated complementary electrochromic device.